The Effect of Combined Factor XI Deficiency with von Willebrand Factor Abnormalities on Haemorrhagic Diathesis - Tavori, Shulamith; Brenner, Benjamin; Tatarsky, llana (Thrombosis and Haemostasis, 1990)
To account for the lack of correlation between the level of factor XI (FXI) in deficient patients and haemorrhagic manifestations, we correlated the prevalence of combined FXI and von Willebrand’s factor (vWF) deficiency in 212 FXI-deficient patients. Fifty-four patients had a combined FXI and vWF deficiency: 16 patients had severe and 38 patients had mild FXT deficiency. In a group of 28 patients with comparably mild FXI deficiency, 14 bleeders had significantly lower mean vWF, Ag, ristocetin cofactor and ristocetin induced platelet aggregation than 14 non-bleeders selected on the basis of comparable FXI levels. These findings suggest that the combination of FXI and vWF deficiency is common and may affect the bleeding tendency in mild FXI deficiency.
Keywords: FXI-deficiency; vWF; Combined factor deficiency